A Controversy of EEG Loreta and NeuroGuide Reports in ObsessiveCompulsive Disorder - Bidaki, Reza; Moosavipoor, Seyed Ahmad; Mirhosseini, Hamid (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
There is a Controversy of EEG Loretaand NeuroGuidereports in obsessive compulsive disorder. In OCD,Alpha at high Alpha group is more than low Alpha group.The controversy is that Alphapower (especially 8 Hz) at Neuroguide low alphagroup is unexpectly morethan high Alpha group but, result on theLoreta mean is oppositeof Neuroguide.